Takhrij and Syarah of Chemistry: The Efficacy of Honey to Cure Disease - Nisrina Dhia Pinasti; Muhamad Fauzi; Dadah Dadah; Yeni Huriani; Nunung Kurniasih (Gunung Djati Conference Series, 2021)
The purpose of this research is to discuss the hadith of the Prophet Muhammad Saw. about the benefits of honey from the perspective of Islam and science. This research method is qualitative through the takhrij and sharah hadith approaches with chemical analysis. The results and discussion of this study is the benefits of honey from a scientific perspective. The conclusion of this research is takhrij and syarah hadith about the benefits of honey from the perspective of Islam and science. From a scientific point of view honey is proven to have many benefits because it contains many active compounds such as vitamin A, vitamin E, vitamin K, phenolic acids and other active ingredients.